2019
DOI: 10.1002/jcp.28482
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers and genetic approaches toward chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease accounts as the leading cause of mortality worldwide prominently affected by genetic and environmental factors. The disease is characterized by persistent coughing, breathlessness airways inflammation followed by a decrease in forced expiratory volume1 and exacerbations, which affect the quality of life. Determination of genetic, epigenetic, and oxidant biomarkers to evaluate the progression of disease has proved complicated and challenging. Approaches including exome sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 164 publications
(200 reference statements)
0
20
0
Order By: Relevance
“…While a few studies about DLM's poisonous quality have been reported, few investigations have been done on the protective agents utilized against such harmfulness and the mechanism of their ameliorative action. In the present examination, the renal wounds produced by DLM might be caused by the OS because of the generation of free radicals …”
Section: Discussionmentioning
confidence: 64%
“…While a few studies about DLM's poisonous quality have been reported, few investigations have been done on the protective agents utilized against such harmfulness and the mechanism of their ameliorative action. In the present examination, the renal wounds produced by DLM might be caused by the OS because of the generation of free radicals …”
Section: Discussionmentioning
confidence: 64%
“…In this study, out of 200 patients, more than three‐ fourth patients, that is, 153 (76.5%) were treated with open reduction and internal fixation which is higher than 17.7% as treated by Bataineh et al 20 A total of 47 patients (23.5%) were treated with a closed reduction which is lower than 82.3% as treated by Bataineh et al . 20 Closed reduction methods have yielded poor esthetic results; therefore, open techniques are increasingly being recognized as an efficient approach for the management of maxillofacial fractures 21,22 …”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is possible to synthesize dendrimers with specific biological and physicochemical properties, as well as to customize the release mechanism of encapsulated molecules from dendrimers. Multiple ligands can also be conjugated, offering them with higher specificity and efficacy in the delivery of various drugs and vaccines [43] , [44] , [50] , [51] . Hence, these unique features of dendrimers make them particularly suitable as the candidates for developing novel drugs and vaccines delivery systems in the management of influenza viral infections.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%